Development and characterization of microsatellite markers in sawih tree (Duabanga moluccana Blume) using ISSR-suppression PCR techniques - Liew, Kit-Siong; Abdullah, Julaihi; Pang Shek, Ling; Ho Wei, Seng (Springer India, 2015)
Duabanga moluccana (or locally known as sawih) is an indigenous fast growing tropical tree species that confers various advantages for the timber industry and for planted forests development. In this paper, we isolated and characterized 8 polymorphic microsatellite markers from the D. moluccana genome using ISSR-suppression PCR techniques. The number of alleles and PIC values ranged from 3 to 8 alleles per locus and from 0.488 to 0.792, respectively. Three microsatellite loci were deviated from Hardy-Weinberg equilibrium (P<0.05). The transferability rate ranged from 24 to 100 % among the three indigenous tree species tested. This indicates that the newly developed microsatellite markers would be useful tools for population genetic studies on D. moluccana and other indigenous tree species.